A Muslim Scholar of the Bible: Prooftexts from Genesis and Matthew in the Qur'an Commentary of Ibn Barrajān of Seville (d. 536/1141). Issue 1 (February 2016) - Casewit, Yousef
Abstract : The Andalusian mystic and Qur'an commentator Ibn Barrajān (d. 536/1141) was one of the earliest scholars of Islam to use the Arabic Bible extensively and non-polemically in his quest to understand the divine Word. This paper assesses his mode of engagement with the Bible and the different strategies he employed to resolve perceived incongruities between narratives of the Qur'an and the Bible. The Bible enjoys the same degree of interpretive authority in Ibn Barrajān's works as Prophetic reports ( ḥadīth ), and there is at least one instance where the Bible not only complements but also challenges his understanding of the Qur'an. Ibn Barrajān's openness to the Bible rests on his principle of 'Qur'anic epistemological supremacy'—that is to say, his reasoning that since the Qur'an is God's untarnished divine revelation, it can serve as the ultimate litmus test against which all other scriptural passages, including the Bible, are to be judged. His far-reaching hermeneutical principle of Qur'anic hegemony was probably partly inspired by the scripturalist-literalist writings of the Ẓāhirī scholar Ibn Ḥazm (d. 456/1064). An exhaustive appendix and translation of the Biblical materials in Ibn Barrajān's works accompanies this paper, confirming beyond reasonable doubt that the Bible used by Ibn Barrajān was translated into Arabic directly from Jerome's Latin Vulgate.